HSV-2 Infection of Human Genital Epithelial Cells Upregulates TLR9 Expression Through the SP1/JNK Signaling Pathway - Hu, Kai; Fu, Ming; Wang, Jun; Luo, Sukun; Barreto, Mariana; Singh, Rubin; Chowdhury, Tasnim; Li, Mei; Zhang, Mudan; Guan, Xinmeng; Xiao, Juhua; Hu, Qinxue (Frontiers in Immunology, 2020)
It is known that herpes simplex virus type 2 (HSV-2) triggers the activation of Toll-like receptor (TLR) 9 signaling pathway and the consequent production of antiviral cytokines in dendritic cells. However, the impact of HSV-2 infection on TLR9 expression and signaling in genital epithelial cells, the primary HSV-2 targets, has yet to be determined. In the current study, by using both human genital epithelial cell lines and primary genital epithelial cells as models, we found that HSV-2 infection enhances TLR9 expression at both mRNA and protein levels. Such enhancement is virus replication-dependent and CpG-independent, while the HSV-2-mediated upregulation of TLR9 does not activate TLR9 signaling pathway. Mechanistically, a SP1 binding site on TLR9 promoter appears to be essential for HSV-2-induced TLR9 transactivation. Upon HSV-2 infection, SP1 translocates from the cytoplasm to the nucleus, and consequently binds to TLR9 promoter. By using specific inhibitors, the JNK signaling pathway is shown to be involved in the HSV-2-induced TLR9 transactivation, while HSV-2 infection increases the phosphorylation but not the total level of JNK. In agreement, antagonism of JNK signaling pathway inhibits the HSV-2-induced SP1 nuclear translocation. Taken together, our study demonstrates that HSV-2 infection of human genital epithelial cells promotes TLR9 expression through SP1/JNK signaling pathway. Findings in this study provide insights into HSV-2-host interactions and potential targets for immune intervention.